Space Astronomy and Astrophysics - Canizares, Claude R.; Savage, Blair D. (Physics today, 1991)
Nearly everything we know about the cosmos comes from studying celestial electromagnetic radiation over roughly 16 decades of wavelength from radio to gamma ray. But most radiation is totally absorbed by our atmosphere—only radio and optical waves penetrate to Earth, and even these are subject to distortion or interference. The ability of space astronomy to escape the effects of Earth's atmosphere has literally opened new windows on the heavens, windows through which we have glimpsed a universe far more diverse than previously known and tantalizingly rich with information about its structure and evolution.